Efficient C-7 or C-3/C-7 Direct Arylation of Tri- or Disubstituted Imidazo[1,2-b]pyrazoles - Grosse, Sandrine; Pillard, Christelle; Bernard, Philippe; Guillaumet, Gérald (Synlett, 2013)
A novel and efficient method of C-7 direct arylation of the imidazo[1,2-b]pyrazole core, never described to date, is presented in this paper. Series of electron-rich or electron-poor aryl and heteroaryl groups were easily introduced. The corresponding products were obtained in moderate to excellent yields thanks to this pallado-catalyzed and microwave-assisted process. A one-pot double C-3 and C-7 direct coupling is also reported.
Keywords: C–C coupling; arylation; fused-ring systems; microwave chemistry; palladium